Implementation Of Game-Based Learning Using Educational Monopoly Games In Fiqh Instruction - Achmad Qusyairi Mahfudi; Ummi Hani (AFKARINA: Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the implementation of Game-Based Learning through an educational Monopoly media in Islamic Jurisprudence (Fiqh) learning and to identify its impact on students' learning motivation, material retention, and critical thinking skills. The study used a qualitative approach with a case study design conducted at Darullughah Wal Karomah Junior High School. The research informants consisted of purposively selected Fiqh teachers and students. Data were collected through observation, in-depth interviews, and documentation. Then, they were analyzed using the interactive model of Miles, Huberman, and Saldaña, which included data condensation, data presentation, and conclusion drawing. Data validity was achieved through triangulation of sources and techniques. The results indicate that implementing Game-Based Learning via educational Monopoly media can increase students' motivation to learn through active engagement in the learning process, strengthen retention of Fiqh material through meaningful, repeated learning experiences, and develop critical thinking skills through problem-solving and collaborative discussions. These findings demonstrate that educational monopoly not only functions as an engaging learning medium but also as a pedagogical strategy that supports active, collaborative, and learner-centered Fiqh learning. This research contributes to the development of innovative game-based Fiqh learning in Islamic education.